IMPROVING STUDENTS’ PARTICIPATION ON LEARNING RECOUNT TEXT THROUGH PEER REVIEW TECHNIQUE - Halimah, Siti; Sada, Clarry; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study wasaimed to know how students? participation in learning recount text improved through peer review technique. The study was conducted through Classroom Action Research which was done in two cycles. The subjects of the research were the English teacher and 16 students of class X MIPA 1 at MA Al-Ma?arifSintang in academic year 2017/2018. The writer used observation checklists and field notes as instruments of data collection. The finding showed that applying Peer Review technique improved students? participation from cycle to cyle. In the first cycle, the students actively participated in learning simple past tense (was/were) in recount text. However, the students? participation in the first cycle was not good enough and most of students were still get low result of participation, the writer conducted the second cycle. In the second cycle, the students improved their participation in learning regular and irregular verbs. In conclusion, students? participation on learning recount text specifically in simple past tense improved through Peer Review technique. Keywords: Students? Participation, Recount Text, Peer Review Technique